2020
DOI: 10.1210/clinem/dgaa780
|View full text |Cite
|
Sign up to set email alerts
|

Total, Bioavailable, and Free 25(OH)D Relationship with Indices of Bone Health in Elderly: A Randomized Controlled Trial

Abstract: Context Questions regarding the superiority of free and bioavailable 25-hydroxyvitamin D [25(OH)D] in predicting health outcomes remain unresolved. Objective This study investigates the impact of vitamin D variables—total, bioavailable, or free 25(OH)D—on indices of bone and mineral metabolism, at baseline and in response to 2 vitamin D doses. Design Our obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…In other studies, the calculated concentrations of free and bioavailable 25(OH)D were lower in men and women with obesity than normal-weight individuals [48], regardless of the method used for these estimations [45,46]. Our study observed significant differences in total, free, and bioavailable 25(OH)D levels among individuals with obesity and VAI (a marker visceral adipose function) in the medium and high tertile.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…In other studies, the calculated concentrations of free and bioavailable 25(OH)D were lower in men and women with obesity than normal-weight individuals [48], regardless of the method used for these estimations [45,46]. Our study observed significant differences in total, free, and bioavailable 25(OH)D levels among individuals with obesity and VAI (a marker visceral adipose function) in the medium and high tertile.…”
Section: Discussionsupporting
confidence: 39%
“…On the other hand, individuals with overweight only presented significant differences in levels of total and bioavailable 25(OH)D. These data on the group of individuals of the health workers are consistent with previous reports that include high BMIs individuals, patients with cirrhosis, nursing home residents, and patients with prediabetes [47] reported to have lower total and free 25(OH)D levels. In addition, in an elderly population, free and bioavailable 25(OH)D do not appear to be superior to total 25(OH)D in predicting indices of bone health [48].…”
Section: Discussionmentioning
confidence: 87%
“…Our study has not performed a formal assessment of PCOS status, with relatively few women showing extreme obesity (mean BMI 25.53 kg/m 2 ) with a 90th percentile BMI of 34.85 kg/m 2 . Notably, we observed a rather weak correlation between vitamin D and PTH concentrations (r = −0.208), similar to El Sabeh et al [34], where coefficients of correlation between PTH and total, bioavailable and free vitamin D ranged from −0.22 to −0.25. It appeared, however, that neither age nor BMI, but at least a two week of holiday leave was the only significant variable that predicted a significant increase in vitamin concentrations after a summer period.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, the strong decrease of 25(OH)D levels with increasing age as a result of decreasing ability of the skin to synthesize cholecalciferol and potentially less exposure to ultraviolet-B radiation is well established [9,17]. By contrast, evidence on potential determinants of specific components of 25(OH)D has been rather sparse and partly conflicting [2,8,18,19]. To our knowledge, ours is the first study to comprehensively assess associations of potential determinants with various components, including non-bioavailable, bioavailable, and free 25(OH)D. The high positive correlations between those measures (and in particular between each of them and total 25(OH)D) and the consistent patterns of associations with potential determinants (apart from genotypes) do not support suggestions for the need to evaluate different 25(OH)D components for assessing vitamin D status in clinical practice in an ethnically homogeneous population, such as our cohort, in which the vast majority of participants were Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have addressed distribution and potential determinants of the various vitamin D biomarkers in different populations [2,3,[6][7][8], evidence from large-scale epidemiological studies among older adults has remained sparse, mostly descriptive without multivariate adjustments [3,8], or limited to single specific vitamin D biomarkers [7]. The aim of this study was to assess distributions and determinants of VDBP, total, bioavailable (and complementary "non-bioavailable"), and free 25(OH)D concentrations in a large population cohort of older adults in Germany.…”
Section: Introductionmentioning
confidence: 99%